The Mixed-Method Approach in Research on War-Related Trauma in the Middle East - Nurzahara Sihombing; M. Agung Rahmadi; Helsa Nasution; Luthfiah Mawar (The Journal General Health and Pharmaceutical Sciences Research, 2025)
This study conducts an in-depth examination of 87 mixed-method studies that address war-related trauma in the Middle East over the past two decades (2000–2023), employing a systematic methodological meta-synthesis approach to formulate a more comprehensive understanding of the impact of armed conflict on affected populations. Quantitative findings indicate an exceedingly high prevalence of post-traumatic stress disorder (PTSD), reaching 73.4% among war refugees (n = 12,456), accompanied by significant comorbidity rates in the form of depression (68.2%) and anxiety disorders (59.7%), both of which clinically exacerbate recovery prognosis. Meanwhile, the thematic qualitative analysis successfully identified five principal dimensions of recurrent traumatic experiences, namely direct exposure to violence (82.3%), the loss of family members (76.9%), forced displacement (71.4%), existential uncertainty regarding the future (68.9%), and the disintegration of social cohesion within affected communities (65.2%). A comprehensive integration of quantitative and qualitative data reveals a substantial correlation between the duration of conflict exposure and the severity of PTSD (r = 0.78, p < 0.001), indicating a linear association between the chronicity of war experiences and the intensity of psychological trauma. Through meta-regression, this study also identifies several statistically significant protective variables that reinforce both individual and collective resilience, including the presence of family support (β = 0.45, p < 0.001), the intensity of religiosity (β = 0.38, p < 0.01), and the strength of community resilience (β = 0.42, p < 0.001), all of which function as moderating factors of traumatic impact. In contrast to the narrow focus of Storozhuk et al. (2023) and Boeije et al. (2013), who emphasized individual trauma, this study advances a broadened paradigm by exploring the collective dimensions of war trauma made possible through an integrative methodological design. While Zerach and Solomon (2016) previously proposed three core categories of traumatic experience, the present study expands the conceptual spectrum by identifying two additional themes and unveiling the complex network of interrelations among trauma elements. The principal novelty of this study lies in the formulation of an integrative model of war trauma that not only theoretically unifies individual and collective dynamics but also constructs a new methodological framework that may serve as a reference point for trauma research in conflict-affected regions marked by the volatile and multidimensional sociopolitical context of the Middle East.